PENDAMPINGAN KADER MENGGUNAKAN MEDIA KARTU KUARTET GUNA MENINGKATKAN PENGETAHUAN TENTANG CARA MENGATASI DISPAREUNIA MENOPAUSE - Iryanti Iryanti; Febri Sri Lestari (Poltekkes Kemenkes Bandung, 2026)
The increasing number of women experiencing menopause has health impacts, one of which is dyspareunia. Prolonged dyspareunia causes stress. Stress can affect the immune system and metabolic processes, making a person more susceptible to heart disease and stroke. These diseases are the leading causes of death among women. One non-pharmacological effort to prevent stress in menopausal women is through education through the use of quartet card games. Integrated health service posts (Posyandu) are places to learn about and implement a healthy lifestyle, however Posyandu RW 08 Kebon Gedang Village does not yet offer a menopause education program. This community service activity aims at broadening the understanding of cadres and women entering menopause about methods for managing dyspareunia that occurs during menopause. The method used was mentoring of Posyandu cadres and menopausal women, which was carried out from June to October 2025, previously conducted a pretest and afterward a posttest. The target consisted of 13 cadres and 7 menopausal women. The results showed an increase in the average knowledge of cadres and menopausal women by 16.85 points. After receiving guidance, the cadres felt more confident in conveying information by using quartet cards as a tool. In conclusion, mentoring motivated cadres and menopausal women to know and try to overcome dyspareunia. Ibrahim Adjie Health Center is recommended to continue coaching the implementation of education using quartet cards in Posyandu, as well as disseminate it to other cadres in its work area.